2016
DOI: 10.1159/000446274
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Vascular Access Care and Surgery Managed by Interventional Nephrologists: A Twelve-Year Experience

Abstract: Background: Optimizing vascular access outcomes is still a challenge, since 30-60% of arteriovenous fistulas fail or do not mature and catheters are widely used in contemporary patients. Methods: This study reports on strategies and outcomes in a single center in which access planning, surgery and maintenance are managed by a team of nephrologists. We retrospectively analyzed 305 fistulas and 61 grafts created in 270 consecutive patients between 2002 and 2013. Results: The percentage of patients receiving a fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
1
6
0
1
Order By: Relevance
“…The mentioned comorbidities were defined previously. 34 VA outcomes were defined in accordance with recommended standards of the Society for Vascular Surgery 35 and the North American Vascular Access Consortium. 36 Primary patency was defined as the time interval from access placement until any intervention to maintain patency, first occurrence of thrombosis, or time of patency measurement.…”
Section: Methodsmentioning
confidence: 99%
“…The mentioned comorbidities were defined previously. 34 VA outcomes were defined in accordance with recommended standards of the Society for Vascular Surgery 35 and the North American Vascular Access Consortium. 36 Primary patency was defined as the time interval from access placement until any intervention to maintain patency, first occurrence of thrombosis, or time of patency measurement.…”
Section: Methodsmentioning
confidence: 99%
“…18 Globally, it has been reported that interventional nephrologists have comparable or even better results than surgeons. 19–23 It seems reasonable to state that dedication to angioaccess surgery is more important than specialty of VA surgeon. The grade of operating surgeon may also influence outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…To date, HD access surgery by nephrologists and its main effects have also been reported [ 12 , 15 – 17 ]. VA surgery and endovascular intervention by nephrologists can improve access outcomes [ 18 ] and timely detection of malfunctions in vascular access, increases the survival of vascular access [ 19 ] and use of AVF, and decreases HD catheter utilization [ 20 ]. In these regards, frequent practice of interventional nephrology may contribute to good survival of HD patients in Japan [ 21 ].…”
Section: Discussionmentioning
confidence: 99%